Does Tube Resistance Compensation Change Metabolic Parameters When Added to Pressure Support Mode During Weaning? - İclal Doruk; Kubilay Demirağ; Mehmet Uyar (Galenos Yayinevi, 2024)
Objective: We postulated that adding tube resistance compensation (TRC) to pressure support ventilation (PSV) would have beneficial effects on metabolic parameters in patients scheduled for weaning. Here, the PSV and PSV+TRC were compared by measuring oxygen consumption (VO2), energy expenditure (EE), and carbon dioxide production (VCO2). Materials and Methods: This was a prospective, randomised, crossover study. Seventy-eight adult patients were randomised to receive either PSV or PSV+TRC. Group 1 consisted of patients that started with PSV initially and then switched to PSV+TRC, whereas Group 2 first received PSV+TRC and then switched to PSV. After 30 minutes of monitoring and stabilization, an indirect calorimeter was connected and metabolic parameters measurement was taken every 5 minutes for 30 minutes, and the last measurement values were recorded at the 30th minute. The patient was then switched to the second treatment mode, and the procedure was repeated. Results: TRC+PSV ventilation had no clinical effects on metabolic parameters compared with PSV (EE, 1746 vs. 1763, respectively; VO2, 255 vs. 260, respectively; VCO2, 206 vs. 208, respectively; all p > 0.05). Conclusion: Adding TRC to PSV did not cause any changes in gas exchange, haemodynamic variables, or metabolic parameters in patients for weaning.